Service-oriented design of environmental information systems - Usländer, Thomas (KIT Scientific Publishing, 2010)
Service-orientation has an increasing impact upon the design process and the architecture of environmental information systems. This thesis specifies the SERVUS design methodology for geospatial applications based upon standards of the Open Geospatial Consortium. SERVUS guides the system architect to rephrase use case requirements as a network of semantically-annotated requested resources and to iteratively match them with offered resources that mirror the capabilities of existing services.
English
Keywords: design methodology; SERVUS; resource orientation; service-oriented architecture; environmental information system